Facial Palsy as Initial Symptom in Glycine Receptor Antibody Positive Progressive Encephalomyelitis With Rigidity and Myoclonus: A Case Report - Wang, Li; Zhang, Rui; Liu, Kai; Xu, Yafang; Song, Bo; Xu, Yuming (Frontiers in Neurology, 2022)
Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a rare and disabling syndrome characterized by painful spasms, myoclonic jerks, hyperekplexia, brainstem signs, and dysautonomia, which is considered to be a severe form of stiff person spectrum disorder (SPSD) and is mostly associated with glycine receptor antibodies. The PERM has an acute or subacute course, with complex and varied initial symptoms mainly manifest as stiffness and pain. The authors present the case of a male patient admitted for intractable stiffness and paroxysmal myoclonus of the lower extremities preceded by a 5-day history of facial weakness. After admission, his symptoms deteriorated rapidly. He developed progressive generalized hypertonia and painful spasms, which quickly spread to the upper extremities, and he suffered frequent paroxysmal myoclonus. Serum and cerebrospinal fluid (CSF) were tested by a cell-based assay, and both were positive for glycine receptor antibodies (GlyR-Abs). The patient developed complications, such as crushed teeth, lumbar vertebral compression fractures, and psoas major muscle abscess, during rapid disease progression, although he responded well after being treated with intravenous methylprednisolone and immunoglobulin. This report of PERM, initiated as facial palsy followed by acute progression, helps to expand the clinical spectrum of this rare autoimmune disorder and raise awareness of the prevention of complications.